The Effect of Work Environment, Commitment and Discipline on Employee Performance at PT. Bank Rakyat Indonesia (Persero) Tbk - Roubun, Rita (Golden Ratio of Human Resource Management, 2021)
Human existence in the organization has a very vital position. The success of an organization is largely determined by the quality of the people working in it. Changes in the environment that are so fast demand their ability to capture the phenomenon of these changes, analyze their impact on the organization and prepare steps to deal with these conditions.